Are public sector workers underpaid in Russia? Estimating the public-private wage gap - Vladimir Gimpelson; Anna Lukiyanova (Institute for the Study of Labor (IZA), 2009)
The paper starts with discussing institutional framework for public sector wage setting in Russia. Given that individual choice of the sector is endogenous to wages, the authors recommend alternative econometric techniques for the public-private wage gap estimation. Applying switching regression that allows correcting for non-random sector selection, the paper provides wage gap estimates for various demographic, occupational, and territorial population subgroups. As it is shown, there is significant cross-group variation in the wage gap. The paper concludes that to eliminate the negative gap wages in the public sector should be linked to the private sector wages at the regional level.
urn:nbn:de:101:1-20090209112
Keywords: J31; J45; 330; Public sector; Lohnstruktur; Besoldung; Öffentlicher Dienst; Privatwirtschaft; Russland